ISLAMIC BRANDING DAN RELIGIUSITAS SERTA PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN OLEH KONSUMEN PADA SWALAYAN AL-BAIK KOTA TANJUNGPINANG - Muhammad Ilham; Firdaus Firdaus (STAIN Sultan Abdurrahman Kepulauan Riau, 2020)
The majority of these Muslims are used by producers. Producers are aware that Muslim consumers are easy targets for marketing their products. One of the strategies that they implemented was Islamic Branding that is using Islamic identity (with the words Islam, Sharia, Islamic names, halal labels) in marketing their products. In this study, the authors used the Correlation type. This research is often referred to as research because, with the aim to find out the relationship between independent variables with accepted variables. This research was built with a mature theory, which serves to know, predict and control a phenomenon. The significance value of Islamic Branding (X1) is 0.667> 0.005, so it can be interpreted so that there is no significant influence between the Islamic Branding variable (X1) on the dependent variable Purchasing Decision (Y). The Significance Value of Religiosity (X2) is 0,150> 0,005, so that it can be interpreted so that nothing shows the significance of the Religiosity variable (X2) to the dependent variable Purchasing Decision (Y). Significant value of 0.240> 0.05, or F Calculate 1.483 <3 , 24 then there is no influence of Islamic Branding (X1) and Religiosity Variable (X2) variables simultaneously on the Purchase Decision variable (Y).